Stochastic modelling and optimization with applications to actuarial models - Li, Mengdi (2012)
This thesis is devoted to Ruin Theory which sometimes referred to the collective ruin theory. In Actuarial Science, one of the most important problems is to determine the finite time or infinite time ruin probability of the risk process in an insurance company.